1996
DOI: 10.1021/jp951200d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diborane Flow Rate on the Structure and Stability of CVD Boron Nitride Films

Abstract: CVD boron nitride films have been deposited at 800 °C from diborane, ammonia, and hydrogen gas mixtures, using different B2H6 flow rates. The effect of the [B2H6]/[NH3] ratio in the gas mixture on the structure, composition, and the stability of the layers in humid atmospheres has been studied. For low [B2H6]/[NH3] ratios (r ≤ 0.25), the deposition rate is low and some crystalline ordering in the deposit was detected. However, when ratios >0.25 are used, stable amorphous boron nitride films are deposited at de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…The N 1s signal at 400.0 eV indicates that the N is bonded to O. [10] Since only one O 1s peak at 533.2 eV is detected in the sample, the tiny amounts of N and O along with the B probably form the B-O-N in the BNWs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The N 1s signal at 400.0 eV indicates that the N is bonded to O. [10] Since only one O 1s peak at 533.2 eV is detected in the sample, the tiny amounts of N and O along with the B probably form the B-O-N in the BNWs.…”
Section: Resultsmentioning
confidence: 97%
“…The corresponding X-ray photoelectron spectroscopy (XPS) spectra show the same presence of B-rich structures from both the elemental and atomic chemical state of the products. [10] in which B-B is the dominant bond in the BNWs. However, no B-N bonds are found (190.6 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Ismach et al reported the growth of atomically smooth h ‐BN layers on Ni substrates at 1025 °C and 135 mTorr; however, nanocrystalline t ‐BN was dominant when grown on Al 2 O 3 . Other research groups have reported the growth of mixed‐phase BN, including amorphous BN ( a ‐BN), t ‐BN, cubic BN ( c ‐BN), wurtzite BN ( w ‐BN), and rhombohedral BN ( r ‐BN), by plasma‐assisted CVD . Overall, a high T g seems to be required for growth on Al 2 O 3 substrates .…”
Section: Introductionmentioning
confidence: 99%
“…The boron precursor was 0.01% diborane (B 2 H 6 ) diluted in H 2 . Diborane and ammonia have been commonly used to produce BN [5]. The B 2 H 6 and NH 3 were separately introduced into the reactor and mixed just above the susceptor to avoid their parasitic gas phase reaction at room temperature [6].…”
Section: Introductionmentioning
confidence: 99%